Dynamic Mechanical Compression of Chondrocytes for Tissue Engineering: A Critical Review - Anderson, Devon E.; Johnstone, Brian (Frontiers in Bioengineering and Biotechnology, 2017)
Articular cartilage functions to transmit and translate loads. In a classical structure-function relationship, the tissue resides in a dynamic mechanical environment that drives the formation of a highly-organized tissue architecture suited to its biomechanical role. The dynamic mechanical environment includes multiaxial compressive and shear strains as well as hydrostatic and osmotic pressures. As the mechanical environment is known to modulate cell fate and influence tissue development toward a defined architecture in situ, dynamic mechanical loading has been hypothesized to induce the structure-function relationship during attempts at in vitro regeneration of articular cartilage. Researchers have designed increasingly sophisticated bioreactors with dynamic mechanical regimes, but the response of chondrocytes to dynamic compression and shear loading remains poorly characterized due to wide variation in study design, system variables, and outcome measurements. We assessed the literature pertaining to the use of dynamic compressive bioreactors for in vitro generation of cartilaginous tissue from primary and expanded chondrocytes. We used specific search terms to identify relevant publications from the Pubmed database and manually sorted the data. It was very challenging to find consensus between studies because of species, age, cell source and culture differences, coupled with the many loading regimes and the types of analyses used. Early studies that evaluated the response of primary bovine chondrocytes within hydrogels, and that employed dynamic single-axis compression with physiologic loading parameters, reported consistently favorable responses at the tissue level, with upregulation of biochemical synthesis and biomechanical properties. However, they rarely assessed the cellular response with gene expression or mechanotransduction pathway analyses. Later studies that employed increasingly sophisticated biomaterial-based systems, cells derived from different species, and complex loading regimes, did not necessarily corroborate prior positive results. These studies report positive results with respect to very specific conditions for cellular responses to dynamic load but fail to consistently achieve significant positive changes in relevant tissue engineering parameters, particularly collagen content and stiffness. There is a need for standardized methods and analyses of dynamic mechanical loading systems to guide the field of tissue engineering toward building cartilaginous implants that meet the goal of regenerating articular cartilage.